2013
DOI: 10.1097/igc.0b013e318276d9da
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the APPRISE Mandate on Use of Erythropoiesis-Stimulating Agents and Transfusion Rates in Patients With Ovarian Cancer Receiving Chemotherapy

Abstract: In our institution, the APPRISE guidelines have resulted in complete cessation of the use of ESAs in patients with primary or recurrent EOC, resulting in considerable cost savings. Importantly, RBC transfusion rates did not significantly increase after the guidelines were imposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
(19 reference statements)
1
2
0
Order By: Relevance
“…This study confirmed findings from prior studies by demonstrating that, after the 2007 NCD, there was a substantial decrease in the concomitant use of CT and ESAs in patients with nonmyeloid cancers and a decrease in ESA administration after the end of CT that persisted until the end of the study period in 2018 7‐15 . In contrast with other studies, our study showed that the full implementation of the ESA REMS in 2011 had minimal impact on ESA administration beyond changes observed after NCD 9,15,17,18 …”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This study confirmed findings from prior studies by demonstrating that, after the 2007 NCD, there was a substantial decrease in the concomitant use of CT and ESAs in patients with nonmyeloid cancers and a decrease in ESA administration after the end of CT that persisted until the end of the study period in 2018 7‐15 . In contrast with other studies, our study showed that the full implementation of the ESA REMS in 2011 had minimal impact on ESA administration beyond changes observed after NCD 9,15,17,18 …”
Section: Discussionsupporting
confidence: 89%
“…Some studies reported either no increase 17 or an increase 9,15,18 in RBC transfusions after REMS implementation. However, these studies examined selected cancers rather than all cancer types 9,15,17,18 and three were small in size 15,17,18 . The study that was conducted in a sample of Medicare patients included fewer than 2000 patients and was restricted to two cancer types 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation